(untitled) (Journal of Human Sciences, 2022)
The topic of this study is focused on the impact of globalization upon the Libyan society in light of the international transformations that international politics witnessed at the end of the eighties and the beginning of the nineties of the last century. Several factors played a role to push the Arab world, especially Libya, to enter into the era of globalization, without adequate preparations. A collective national agenda to deal with the challenges and dangers was planned. They were made in the form of increasing pressures and multiple forms and goals, which greatly reduced the margin of independence and worked to crack the Arab alliance, However, this study came to shed light on this phenomenon and its impact on the value-building of the Libyan society. The historical and descriptive method was used to identify the historical roots, analyze and characterize this phenomenon in order to reach the most important factors affecting the society. This became clear through this study that political globalization, as a phenomenon characterized by rapid exchange and alteration as it is the product of ideological ideas. What globalization now proposing is only for the sake of exchanging and alternating the conflict from an ideological conflict to a cultural, intellectual conflict in the first place. This requires call for the need to preserve social values and customs that increase adherence to identity and social loyalty. The study concluded that there should be a need for a permanent relationship between social loyalty and political loyalty. This is done by focusing on the issue of social upbringing and political education. Such process would constitute the main support for political and social development to confront globalization and its multiple theses. The study also recommended the need to adhere to social and historical values which will reduce the rush of globalization towards the foundations of those societies and their inherited values.